Flow and Heat Transfer of a non-Newtonian Fluid: a Numerical Approach using Lie Scale Transformation Technique - Anitha, V.; Prasad, Ramakrishna (Journal of Applied Nonlinear Dynamics, 2026)
In this study, the solutions are provided for steady, incompressible, and electrically conducting non-Newtonian fluid flow over a stretching surface embedded in a porous medium with variable viscosity in the presence of a uniform transverse magnetic field, a heat source/sink, and Joule heating. With the Scaling group transformations, we transformed the non-linear coupled partial differential equations into coupled ordinary differential equations. Symbolic algebra software Maple was used to illustrate the effects of embedded variables on the distribution of velocity and heat functions, and a comparison of skin friction and temperature gradient was conducted using a table.